Cap-and-innovate: Evidence of regulation-induced innovation in California - Vanessa da Cruz (ETH Zurich, CER-ETH - Center of Economic Research, 2022)
The paper applies the synthetic control method to examine the effects of California's Capand-Trade Program on environmental innovation. The analysis exploits the International Patent Classification system to identify patents relating to environmentally sound technologies. This enables the study to focus on the effects of the policy intervention on green patent filings. A counterfactual is constructed by the combination of other states in the US which allows the comparison of patent applications in California to the estimated counterfactual situation in the absence of a Cap-and-Trade program. The study finds that the number of patents related to green technologies increased by approximately 22.5% after the passing of the Cap-and-Trade regulation. This result is robust to alternative specifications of the synthetic control method.
Keywords: Q55; Q58; O31; O38; 330; Induced Innovation; Environmental Policy; Climate Change; California Cap-and-Trade Program